2022
DOI: 10.1111/exsy.13126
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network and symmetric key cryptography based verification protocol for 5G enabled Internet of Things

Abstract: Driven by the requirements for entirely low communication latencies, high bandwidths, reliability and capacities, the Fifth Generation (5G) networks has been deployed in a number of countries. One of the most prevalent application scenarios of 5G networks is the Internet of Things (IoT) that can potentially boost convenience and energy savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…However, this protocol is susceptible to modification, replay, MitM and impersonation attacks. The multi-party access mechanism by Zhang et al [32] also incurs high processing overheads [33] when large numbers of IoT devices are deployed. This problem can be addressed by the protocol developed by Ali et al [34] , which is shown to have less computation overheads and high throughputs.…”
Section: Related Workmentioning
confidence: 99%
“…However, this protocol is susceptible to modification, replay, MitM and impersonation attacks. The multi-party access mechanism by Zhang et al [32] also incurs high processing overheads [33] when large numbers of IoT devices are deployed. This problem can be addressed by the protocol developed by Ali et al [34] , which is shown to have less computation overheads and high throughputs.…”
Section: Related Workmentioning
confidence: 99%
“…The prediction of cancer at early stages is essential as it can simplify the subsequent clinical requirements of patients and determining the effective treatment [12] . Various techniques such as clinical (traditional) techniques [21] and machine learning algorithms [22] have been proposed by researchers for early detection and prediction of breast cancer.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, quantum nearest mean classifier has utilized the binary classification where quantum version is employed to estimate the optimal performance measures [43] . Early studies in the area of QML by Zhang and Ni [22] have shown that QML is one of the most promising technologies of research in the future. The experimental demonstration in the field of quantum computing has made remarkable interests in the recent years, giving rise to new striking possibilities of enhancing machine learning with quantum devices [53] .…”
Section: Consumes Timementioning
confidence: 99%
“…The proposed model is validated using the benchmark dataset and the results are examined in terms of precision, recall, accuracy, and F1-score. Nyangaresi et al, 2022 deploy an ANN for target cell selection in a 5G network, and authentication of communicating entities takes place before being admitted in the new cell. It has a low packet loss ratio and latency variations.…”
mentioning
confidence: 99%
“…Nyangaresi et al, 2022 deploy an ANN for target cell selection in a 5G network, and authentication of communicating entities takes place before being admitted in the new cell. It has a low packet loss ratio and latency variations.…”
mentioning
confidence: 99%